Cytotaxonomic considerations on the sex chromosome variation observed within Acomys ngurui Verheyen et al. 2011 (Rodentia Muridae) - Castiglia, Riccardo; Annesi, Flavia (Zootaxa, 2012)
The taxonomy of the East African Muridae belonging to the Acomys spinosissimus Peters 1852 species complex has been recently revised (Verheyen et al., 2011). Two new species have been described by means of external morphologic analysis, craniometry, enzymes, mitochondrial DNA sequences and karyological information. For one of the two new species, Acomys ngurui Verheyen et al. 2011, a polymorphic karyotype has been observed. In fact, for 19 of the 22 karyotyped individuals, the karyotype is identical to the one described for A. spinosissimus s. s. (2n = 60, aFN = 68), characterized by a sex chromosome constitution of the XX/XY type, with an acrocentric X and a submetacentric Y (Dippenaar and Rautenbach, 1986). The remaining three females possess a karyotype that resembles the one reported by Matthey (1965) and Barome et al. (2001) characterized by a unique giant metacentric X chromosome (Xg), and by a variable diploid number (2n = 59–62). These females were found in the three localities in Tanzania together with specimens with the typical ‘spinosissimus’ karyotype. Specimens carrying the Xg were not distinguishable on the basis of their mtDNA sequence or morphology from the other specimens with XY karyotype (Verheyen et al., 2011). The authors concluded that the available evidence did not allow one to give taxonomic value to this chromosomal configuration, characterized by a particular sex determination, hoping for future work that will study the animals bearing this typical karyotype in more detail.